Protein structural alterations in diabetic cavernosal tissue - their role in erectile dysfunction progression - Castela, A. (2011)
Erectile dysfunction (ED) is one of the most prevalent complications in diabetic men. Hyperglicemia contributes to increased oxidative stress (OS) in diabetic corpus cavernosum (CC), promoting alterations in cavernosal cellular components. However, it remains unclear the mechanisms by which OS induces modifi cations in diabetic penile tissue with the progression of diabetes and its role in the devel opment of ED. We intended to evaluate/quantify CC protein structural modifi cation caused by OS in an early and late stage of diabetes.